HUBUNGAN INDEKS MASA TUBUH DENGAN SIKLUS MENSTRUASI PADA REMAJA DI DESA LUBUK SOTING - Andria, Andria; Fitria, Rahmi; Herawati, Rika; Suraidah, Suraidah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
An unbalanced nutritional status, either too low or too high, risks disrupting the balance of reproductive hormones such as estrogen and progesterone, which can ultimately lead to menstrual cycle irregularities. This study aims to determine the effect of BMI on the menstrual cycle in adolescent girls in Lubuk Soting Village. This study used an analytical design with a cross-sectional approach. The sampling technique was total sampling (saturated sample), meaning that the entire population that met the criteria was included as a sample, with a total of 30 respondents. Data collection was carried out through questionnaires and direct measurements of weight and height. Data analysis was carried out using univariate and bivariate methods. In the bivariate analysis stage, an independent t-test was used. The results showed that the majority of respondents (60%) had an abnormal BMI and 66.7% experienced irregular menstrual cycles. Based on the results of the independent t-test, a p-value of 0.003 was obtained, indicating a significant difference between BMI and menstrual cycle regularity. This means that BMI has a significant influence on menstrual cycle conditions in adolescents. Based on these results, it can be concluded that maintaining BMI within the normal range is very important to support menstrual cycle regularity. Teenagers are advised to adopt a balanced diet and engage in regular physical activity as part of efforts to maintain reproductive health.Keywords: Body Mass Index (BMI), Menstrual Cycle, Adolescents